EVALUATION OF ANTIBACTERIAL ACTIVITY OF ROSMARINUS OFFICINALIS L. ESSENTIAL OIL - GAYATRI M.C; SUDHA U; SHUBHA J; SURESH R (International Journal of Pharma and Bio Sciences, 2014)
The antibacterial activity of crude and essential oil extract of rosemary (Rosmarinus officinalis L.) against the infectious bacteria viz., Escherichia coli, Bacillus subtilis, Pseudomonas spp and Staphylococcus aureus were evaluated in vitro. It was found that rosemary oil exhibits high antibacterial activity against E. coli, B.subtilis, S.aureus, and Pseudomonas spp, when compared to crude extract. The in vitro Minimum Inhibitory Concentration (MIC) of rosemary oil was found to be 100μg ml-1 for inhibiting the growth of Pseudomonas spp; 50μg ml-1 for inhibiting the growth of B. subtilis and S. aureus whereas, it was found to be 12.5μg ml-1 for E. coli. The statistical analysis for MIC of R. officinalis oil was found to be 42.82µg/ml for inhibiting the growth of B.subtilis and S. aureus, it was found to be 10.88µg/ml for E.coli and 85.66µg/ml for Pseudomonas spp